Konsep Sistem Pendukung Keputusan & Pengembangan Sistem Informasi Media Sosial Dalam Menghasilkan Framework Empathy Netizen - Mardella Maulida Nurdayana; Suharnomo Suharnomo (STMIK Budi Darma, 2022)
Social media is growing very rapidly in the current era of globalization. This development requires a guide to be able to manage the flow of communication well on social media. In this study, the method used is honeycomb, what is social media listening? and Daniel Goleman, these three concepts will be able to produce a netizen empathy framework on social media. Furthermore, this research is also a development of previous research: Designing the Concept of Leaderships Intelligence (CI2.1) Version 2.0 inside social media Using Ken Watanabe Problem Solving 101 Methods. If the previous research discussed the categories of leadership in social media in detail, then in this follow-up study, how do we apply the concept of empathy in communication so that it can produce netizens who can provide solutions to the community. Problems such as: understanding each other in communication is still something that must be discussed and given a solution, listening and providing solutions are also important things that must be discussed and giving an opinion and proper assessment of a comment or criticism is also a problem that must be addressed immediately. The results of this study are a framework and guide so that netizens can improve the quality of empathy in communication, provide solutions and other things that can be used positively in order to form a positive environment on social media and produce creative solutions.